Pelatihan Pemanfaatan Dan Penerapan Teknologi Sebagai Bentuk Implementasi Program Kampus Mengajar 5 Di SDN 03 Kranggan, Malang - Rosita Dwi Ferdiani; Wahyudi Harianto; Fahmi Arif Zakaria (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
The Merdeka Campus Program is intended for students from various majors and tertiary institutions throughout Indonesia. The Teaching Campus Program at SDN 03 Kranggan was attended by 5 students from Malang State University and Malang Islamic University. One of the programs held by students is training in the use and application of technology for teachers at SDN 03 Kranggan, Ngajum, Malang. This activity was carried out on May 27 2023 in a class 5 room at SDN 3 Kranggan. This activity was attended by 9 school teachers and campus students teaching as presenters. The response from the teachers seemed enthusiastic in participating in this activity. Based on the results of the training on the use and application of technology, it showed an increase in teacher competence before and after training. application of technology, it showed an increase in teacher competence before and after training.